Asas Peradilan Sederhana, Cepat, dan Biaya Ringan dalam Gugatan Perceraian di Pengadilan Agama Pamekasan: kajian Putusan Nomor 0862/Pdt.G/2015/PA. Pmk - Sofian Syaiful Rizal (Universitas Nurul Jadid, 2019)
This study aims to analyze court decisions, in divorce lawsuits that use simple, fast and low-cost judicial principles at the Pamekasan Religious Court. The problems that arise from this study are, First, what is the legal foundation of judge in resolving divorce claims in religious courts using simple, fast and low-cost judicial principles? Second, what are the legal considerations of religious courts in examining, hearing, and deciding divorce cases in religious courts? The research method uses a normative juridical approach. The results of the study show that: First, the principle of justice is simple, fast, and low cost refers to Law No. 4 of 2004 concerning Judicial Power article 4 paragraph (2), and article 5 paragraph (2). Also contained in Law No. 7 of 1989 in article 57 paragraph (3), as well as in article 58 paragraph (2). Second: The legal considerations of the extreme religious court in rejecting a divorce lawsuit in a religious court are in accordance with the legal basis of state legislation and syar'i law. Considering, based on the testimonies of the witnesses, that the dispute between the plaintiff and the defendant only happened once, so that it did not meet the criteria of article 19 letter C, namely continuous disputes and arguments so that there was no hope of living in harmony again. Keywords: Judicial Principles, Divorce Lawsuit, Judge's Decision